Toyota Process Flow Analysis (Global Journal of Management and Business Research, 2016)
Toyota is a world class company that is known for its quality practices and the production and supply chain is diligently managed so that it can meet its customer demand well on time. The company strategies are well supported through comprehensive production process so that it can manage cost efficiency, drive better quality output vehicles and to manage the high class operational environment. Toyota can further enable Just-in-Time and Total Quality Management practices so that it can help improve productivity, manage high quality standards and able to meet customer demand well on time. Company can further develop predictive metrics, drive transformation and put high quality standards to further manage its production and supply chain to meet competitive standards.
Keywords: manufacturing; process flow; activities; inputs; output; TQM (total quality management); TPS (toyota production system)